2013
DOI: 10.1248/cpb.c13-00202
|View full text |Cite
|
Sign up to set email alerts
|

Saponins Esculeosides B-1 and B-2 in Italian Canned Tomatoes

Abstract: Italian canned tomatoes contain the tomato glycosides esculeosides B-1 (1, 0.0052%) and B-2 (2, 0.0068%) without esculeoside A. Herein, the structure of esculeoside B-1 (1) is characterized to be 3-O-β-lycotetraosyl (5S,22R,23S,25S)-22,26-epimino-16β,23-epoxy-3β,23,27-trihydroxycholestane 27-O-β-d-glucopyranoside. We hypothesized that these substances might be derived from esculeoside A when the cans are prepared with treatment in boiling water. To confirm that hypothesis, we refluxed esculeoside A with water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…The configuration of the hydroxyl group at C-23 was estimated as β-axial because the H 3 -21 signals stayed at δ 1.26 in the usual chemical shift, whereas it appeared at δ 1.59 in a 1,3-diaxial correlation 11) with the C-23-OH group in esculeogenin B 2 (5). Therefore, the structure of 4 could be represented as (5α,22S,23S,25S)-22,26-epimino-16β,23-epoxy-3β,23,27-trihydroxycholestane, and the configuration at C-22 in esculeoside B-1 (2) 8) should be revised to S from R. Thus, we have shown that tomato juices packaged in plastic bottles contain tomato saponins, esculeosides B-1 (2) and B-2 (3), which provide esculeogenins B 1 (4) and B 2 (5), respectively, by 2 N HCl hydrolysis. We concluded that tomato saponins in juice packaged in plastic bottles were derived from esculeoside A (1) when the juiceis processed with boiling water.…”
Section: Saponins Esculeosides B-1 and B-2 Inmentioning
confidence: 97%
See 3 more Smart Citations
“…The configuration of the hydroxyl group at C-23 was estimated as β-axial because the H 3 -21 signals stayed at δ 1.26 in the usual chemical shift, whereas it appeared at δ 1.59 in a 1,3-diaxial correlation 11) with the C-23-OH group in esculeogenin B 2 (5). Therefore, the structure of 4 could be represented as (5α,22S,23S,25S)-22,26-epimino-16β,23-epoxy-3β,23,27-trihydroxycholestane, and the configuration at C-22 in esculeoside B-1 (2) 8) should be revised to S from R. Thus, we have shown that tomato juices packaged in plastic bottles contain tomato saponins, esculeosides B-1 (2) and B-2 (3), which provide esculeogenins B 1 (4) and B 2 (5), respectively, by 2 N HCl hydrolysis. We concluded that tomato saponins in juice packaged in plastic bottles were derived from esculeoside A (1) when the juiceis processed with boiling water.…”
Section: Saponins Esculeosides B-1 and B-2 Inmentioning
confidence: 97%
“…Such tomatoes contain tomato saponins, rare, naturally occurring steroidal solanocapsinetype glycosides, a 0.095% mixture of esculeosides B-1 (2) and B-2 (3) lacking esculeoside A (1). 8) We refluxed esculeoside A (1) with water for 6.5 h, providing a mixture of esculeosides B-1 (2) and B-2 (3) quantitatively; therefore, we hypothesized that these substances might be derived from esculeoside A (1) when the cans are processed with boiling water. 8) In the present study, we analyzed the amount of tomato saponin in tomato juice commercially processed in 900 g plastic bottles to compare the respective ingredients in each bottles.…”
Section: Saponins Esculeosides B-1 and B-2 Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we found a new method for the respective conversions of 1 or a mixture of esculeosides B-1 (2) and B-2 (3) 6) to the pregnane derivative as follows: Esculeoside A (1) was refluxed in 1 N KOH for 1 h. The reaction mixture was separated by silica gel column chromatography using a mixture of CHCl 3 -MeOH-H 2 O (8 : 2 : 0.2) to afford the major product (4) On the other hand, a mixture of esculeoside B-1 (2) and esculeoside B-2 (3) was refluxed in 1 N KOH for 1 h. After neutralizing with 1 N HCl, the reaction mixture was concentrated under reduced pressure and passed through Diaion HP-20 to afford the crude material, which was purified by using silica gel chromatography using a mixture of Next, compound 4 was refluxed in 2 N HCl-MeOH for 1 h, and the resulting reaction mixture was purified by silica gel column chromatography using a mixture of n-hexane-acetone H-NMR spectrum (in CDCl 3 ) showed three methyl groups at δ 0.77 (3H, s), 0.81 (3H, s), and 2.18 (3H, s); an oxygen-bearing methane proton at δ 3.53 (1H, m); and an olefinic proton at δ 6.62 (1H, dd, J=1.8, 3.1 Hz). Moreover, the 13 C-NMR spectrum showed a total of 21 carbons including three methyl groups at δ 12.2, 15.9, and 28.5; one oxygen-bearing methine carbon at δ 71.3; two olefinic carbons at δ 144.4 and 155.5; and a carbonyl carbon at δ 196.8.…”
mentioning
confidence: 99%